PRAKTIK PENGASUHAN ANAK PADA KELUARGA PETANI PESERTA BINA KELUARGA BALITA (BKB) MELATI 3 DI DESA NGUKEN KECAMATAN PADANGAN KABUPATEN BOJONEGORO - Putri, Visca Dwi (BELIA: Early Childhood Education Papers, 2012)
BKB is a media service that has different types of activities, namely extension and playing with tools EduaktifGames. This effort aims to increase knowledge and awareness of mothers and other family members about theimportance of the process of growth and development of infants and to improve the skills of mothers and otherfamily members in obtaining the optimal development of the child, including mental stimulus usingeducational games.The purpose of this study was to determine the model parenting BKB Melati 3 in the Village District NgukenPadangan Bojonegoro, to determine the extent of the application of the parenting BKB Melati 3 on peasantfamily in the village district Nguken Padangan Bojonegoro.The approach used in this study is descriptive qualitative, using interviews and observations as well asdocumentation of the image field. Subjects used for research investigators totaled nine parents and 9 children. The results of this study are parenting counseling BKB from the aspects of child development child developmentlate because if the parents did wrong in parenting. By looking at the child development BKB cadres can takeaction to explain the correct way of parenting by looking at the child's development. Parents are not parentingpractice with maximum economic reasons families so that children are nurtured and trained rare fordevelopment. Many parents assume that children will grow by it self because it has been trained in the BKBwithout havingto be trained at home.Conclusions from the study the researchers did was care Nguken peasant family in the village can not do asmuch as possible because of busy work and more parents use the permissive parenting. BKB better parentingpractices lead to the development of children because of the knowledge of child development then can be wellcared for by the child's parents or not. The authors suggested that the - those involved in caregiving to establishgood communication between parents and volunteers BKB.